Pengaruh Minat Baca Dan Pemanfaatan Perpustakaan Terhadap Prestasi Belajar (Studi Kasus Pembelajaran IPS di MTsN 5 Kediri) - Arina Widia Ningtias; Anggoro Putranto (Departement of Mathematics Education, 2024)
This research aims to determine the influence of students' use and interest in reading, especially in supporting the social studies learning process, on student learning achievement at MTsN 5 Kediri. Using quantitative methods and data analysis using SPSS. The results of the research show that there is an influence of library use and interest in reading on student learning achievement in class VIII in social studies subjects which can be seen by the results obtained F Count > F table (6.322 > 3.12) with a significance of 0.003 < 0.05, so that H0 is rejected and Ha is accepted, which states that the variables of library use and interest in reading influence student learning achievement. These findings provide valuable guidance for developing more effective, efficient and attractive library use and interest in reading for students in the educational era in order to support optimal learning achievement.